Newspaper style - Khazratkulova F. T. (Zien Journals, 2022)
In this article, the conception of newspaper, the characteristics of newspaper style, clichés and phrases, and their importance in the newspaper, the evaluation of newspaper clichés and phrases in newspaper context are given.
Keywords: stylistics,; newspaper; functional styles; official style; publicistic style; scientific style